Oil Volatility and Economic Growth: Evidences from Top Oil Trading Countries - Bagadeem, Salim (International Journal of Energy Economics and Policy, 2023)
The research attempts to delve further into the relationship of oil volatility and economic growth of top oil exporting and importing countries. Annual time series data on oil prices and economic growth (1987-2022) has been considered for top 5 exporting and importing countries. Basic statistical techniques and VAR regressions have been used to analyze data. The relationship between volatility and economic activity was found to be more significant for exporting countries rather than importing countries and a lag effect on 6 years is observed as optimal in this relationship. The global financial crisis was observed as an insignificant event on oil volatility (contrary to Ftiti et al.,2016). One of the significant finding of the study is that Japan’s economic growth is positively associated with the long term oil price volatility.